The Effect of a Life Skills Training Program on Students’ Self-Determination - Kolovelonis, Αθανάσιος; Goudas, Μάριος; Dimitriou, Ελένη; Gerodimos, Βασίλειος (Inquiries in Physical Education and Sport, 2006)
The purpose of the present study was to examine the effect of a life skills training program taught in physical education settings on students’ self-determination. Of the 73 secondary school participants, 35 comprised the initial experimental group and the 38 the initial control group. After the implementation of the intervention with the initial experimental group, the groups were reversed and the initial control group went on to receive the intervention. The life skills program included goal setting, the positive thinking / self-talk and was carried out in connection with a program for the development of the students’ physical fitness. In order to assess students’ self-determination, the self-determination questionnaire in physical education (Goudas et al., 2000) was used. The results showed that students’ self-determination increased in both groups after the intervention in each part of the study and the improvement retained in the initial experimental group in the second part of the study. In conclusion, teaching life skills through physical education can improve students’ self-determination.